До питання про якість та її забезпечення: концептуальні розвідки у зарубіжжі та здобутки України - Олена Локшина (Pavlo Tychyna Uman State Pedagogical University, 2013)
Проаналізовано позицію міжнародних організацій щодо проблеми якості освіти та її забезпечення у світлі глобалізаційних трансформацій ХХІ століття; висвітлено погляди зарубіжних учених на феномен якості освіти через призму багатогранності; проведено порівняння з Україною на рівні нормативних ініціатив і практичних здобутків. Проанализирована позиция международных организаций относительно проблемы качества образования и его обеспечения в свете глобализационных трансформаций ХХІ столетия; освещены взгляды зарубежных ученых на феномен качества образования через призму многогранности; проведено сравнение с Украиной на уровне нормативных инициатив и практических достижений. The position of international organizations, i.e. UN, UNESCO, European Union in relation to the problem of education quality and its assurance under globalization transformations of the ХХІ century is analyzed. It is proved that the educational initiatives of all American presidents are oriented to the educational services quality upgrading after the sputnik launch by the USSR in 1957. A conclusion is made that the education quality is considered as one of the ХХІ century priorities by the world community. The foreign scholars' ideas to the education quality phenomenon through the many-sided prism are highlighted. The approaches («input-process-outcome»; «child-centered»; «multi-level public reciprocity») to the development of a high quality education system are analyzed. Comparison with Ukraine at the level of normative initiatives and practical achievements is conducted. The attention is paid to the fact, that along with the declaration of the importance of education quality in Ukraine at state level, a great number of issues which lie both in theoretical (development of education quality concept) and practical dimensions (development of valid tests, preparation of skilled personnel, financing) is remained unsolved. All of this makes the world expertise topical.